Nurturing compassion in schools: A randomized controlled trial of the effectiveness of a Compassionate Mind Training program for teachers - Matos, Marcela; Albuquerque, Isabel; Galhardo, Ana; Cunha, Marina; Pedroso Lima, Margarida; Palmeira, Lara; Petrocchi, Nicola; McEwan, Kirsten; Maratos, Frances A.; Gilbert, Paul (PLOS ONE, 2022)
Objectives Schools are experiencing an unprecedented mental health crisis, with teachers reporting high levels of stress and burnout, which has adverse consequences to their mental and physical health. Addressing mental and physical health problems and promoting wellbeing in educational settings is thus a global priority. This study investigated the feasibility and effectiveness of an 8-week Compassionate Mind Training program for Teachers (CMT-T) on indicators of psychological and physiological wellbeing. Methods A pragmatic randomized controlled study with a stepped-wedge design was conducted in a sample of 155 public school teachers, who were randomized to CMT-T (n = 80) or a waitlist control group (WLC; n = 75). Participants completed self-report measures of psychological distress, burnout, overall and professional wellbeing, compassion and self-criticism at baseline, post-intervention, and 3-months follow-up. In a sub-sample (CMT-T, n = 51; WLC n = 36) resting heart-rate variability (HRV) was measured at baseline and post-intervention. Results CMT-T was feasible and effective. Compared to the WLC, the CMT-T group showed improvements in self-compassion, compassion to others, positive affect, and HRV as well as reductions in fears of compassion, anxiety and depression. WLC participants who received CMT-T revealed additional improvements in compassion for others and from others, and satisfaction with professional life, along with decreases in burnout and stress. Teachers scoring higher in self-criticism at baseline revealed greater improvements post CMT-T. At 3-month follow-up improvements were retained. Conclusions CMT-T shows promise as a compassion-focused intervention for enhancing compassion, wellbeing and reducing psychophysiological distress in teachers, contributing to nurturing compassionate, prosocial and resilient educational environments. Given its favourable and sustainable effects on wellbeing and psychophysiological distress, and low cost to deliver, broader implementation and dissemination of CMT-T is encouraged.